Emergency Medicine Reports' LLSA Exam Study Guide 2020 - Mark, Shelly (Emergency Medicine Reports' LLSA Exam Study Guide Ser., 2019)
With tens of thousands sold since inception, Emergency Medicine Reports' LLSA Exam Study Guides are widely recognized as dependable, authoritative, and convenient resources for ABEM Lifelong Learning and Self-Assessment (LLSA) test prep. Featuring article texts and useful study tools, Emergency Medicine Reports' LLSA Exam Study Guide 2020 also comes with the chance to earn CME while you study.